Unlocking the Secrets of Valvular Heart Disease: A Journey through the World of Imaging Modalities (Bangladesh Heart Journal, 2024)
Valvular heart disease is a prevalent and clinically significant condition with potential complications and adverse outcomes if left untreated or poorly managed. Accurate assessment of valve structure, function and hemodynamics is crucial for effective evaluation and management of valvular heart disease. In this systematic review, we provide a comprehensive overview and comparison of imaging modalities used in the assessment of valvular heart disease.The introduction highlights the background and significance of valvular heart disease, emphasizing its impact on cardiovascular health, global prevalence, and associated complications. Furthermore, it emphasizes the importance of imaging modalities in the evaluation and management of valvular heart disease, discussing their role in providing crucial information for accurate diagnosis, risk stratification, treatment planning, and monitoring.The objective of this review article is to summarize the strengths, limitations and diagnostic accuracy of different imaging modalities in valvular heart disease assessment. We present detailed discussions on echocardiography, computed tomography (CT) imaging, nuclear imaging techniques and emerging imaging modalities, such as 3D echocardiography, strain imaging and fusion imaging. Each section explores the specific role of the imaging modality, its advantages, limitations and diagnostic accuracy in the evaluation of valvular heart disease.Additionally, we provide a comparative analysis of these imaging modalities, highlighting their strengths, weaknesses and specific indications. The integration of multiple imaging modalities for a comprehensive evaluation in specific scenarios is also discussed, emphasizing the complementary roles of different modalities in optimizing diagnostic accuracy and treatment planning.The review concludes with implications for clinical practice and future research directions. It underscores the importance of selecting the appropriate imaging modality or combination of modalities based on individual patient characteristics and clinical needs. Furthermore, it highlights the potential clinical impact of emerging imaging techniques and the need for standardization, cost-effectiveness studies, and further research to optimize the utilization of imaging modalities in valvular heart disease management.Bangladesh Heart Journal 2023; 39(1): 49–56